The Protection Potential of Antioxidant Vitamins Against Acute Respiratory Distress Syndrome: a Rat Trial - Erol, Nazli; Saglam, Leyla; Saglam, Yavuz Selim; Erol, Huseyin Serkan; Altun, Serdar; Aktas, Mustafa Sinan; Halici, Mesut Bunyami (Springer Science and Business Media LLC, 2019)
Acute respiratory distress syndrome (ARDS) is a fatal disease that includes inflammation formed by septic and non-septic causes. Reactive oxygen radicals (ROS) play a key role in ARDS pathophysiology and constitute the base of damage process. Antioxidant vitamins are used for inhibiting hazardous effects of radicals. Therefore, effects of antioxidant vitamins such as α-lipoic acid (ALA), vitamin E (VITE), and C (VITC) were investigated on oleic acid (OA)-induced ARDS rat model. Furthermore, high and low dose of methylprednisolone (HDMP, LDMP) was used for comparing effects of the vitamins. In this study, 42 male rats were divided to seven groups named control, OA, ALA, VITE, VITC, LDMP, and HDMP. OA was intravenously administered to all groups except control group and other compounds were orally administered (ALA, VITE, and VITC: 100 mg/kg, LDMP: 5 mg/kg, HDMP: 50 mg/kg) after OA injections. OA increased MDA level in lung tissue and TNF-α and IL-1β cytokine levels in serum. ALA, VITE, VITC, and both dose of MP significantly decreased the cytokine levels. Although OA reduced SOD, CAT, and GSH levels in lung tissue, the vitamins and LDMP markedly enhanced the levels except for HDMP. Furthermore, OA showed thickening in bronchi and alveolar septum, hyperemia in vessels, and inflammatory cell infiltrations in lung tissue histopathological examinations. Antioxidant vitamins may be useful for premedication of ARDS and similar disorders. However, methylprednisolone was not found sufficient for being a therapeutic agent for ARDS.
Keywords: Male; Premedication; Vitamins; Protective Agents; Severe Acute Respiratory Syndrome; Methylprednisolone; Antioxidants; Rats; Animals; Oleic Acid; 3. Good health